1995
DOI: 10.1128/aac.39.6.1295
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial activity of a new antiulcer agent, ecabet sodium, against Helicobacter pylori under acidic conditions

Abstract: Helicobacter pylori NCTC 11637, which is nonviable at pH 3.0, became viable after addition of 10 mM urea owing to ammonia production by urease. In a buffer supplemented with urea, ecabet sodium decreased both the production of ammonia and the number of viable cells of H. pylori NCTC 11637 and changed the bacteria from the bacilliform to the horseshoe or doughnut shape in a concentration-dependent manner. In particular, ecabet sodium (2 and 4 mg/ml) decreased the number of viable cells below the control level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 27 publications
0
55
1
Order By: Relevance
“…Ecabet sodium exhibits a bactericidal effect against H. pylori by inhibiting the urease activity of the bacterium, or by a direct bactericidal effect under acidic conditions. 16 On the other hand, it has been reported that the D 13 C‰ in the UBT is significantly decreased after 4 weeks of administration of sucralfate. 17 In the present study, mucoprotective agents, such as polaprezinc, rebamipide, teprenone, cetraxate hydrochloride, sucralfate, and ecabet sodium, were evaluated for their possible effects on the results of the UBT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ecabet sodium exhibits a bactericidal effect against H. pylori by inhibiting the urease activity of the bacterium, or by a direct bactericidal effect under acidic conditions. 16 On the other hand, it has been reported that the D 13 C‰ in the UBT is significantly decreased after 4 weeks of administration of sucralfate. 17 In the present study, mucoprotective agents, such as polaprezinc, rebamipide, teprenone, cetraxate hydrochloride, sucralfate, and ecabet sodium, were evaluated for their possible effects on the results of the UBT.…”
Section: Discussionmentioning
confidence: 98%
“…[15][16][17] While the mechanism of action varies among drugs, these drugs are said to have direct antimicrobial activity, to inhibit the adhesion of H. pylori to the gastric mucosa, to inhibit the urease activity of H. pylori, to inhibit the protease/lipase activity of H. pylori, or to enhance the antimicrobial activity of antibiotics. 15 It is, therefore, necessary to determine whether mucoprotective agents can produce false-negative results in tests for H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Bactericidal activity was determined by using an in vitro killing assay (25,29,37). A bacterial suspension of H. pylori NCTC 11638 (100 µl, approximately 10 7 CFU/ml) was inoculated into 10 ml of 0.2% DMCD-supplemented PPLO broth alone or containing TG-I (12.5 to 50 µg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of pH on the antibacterial activity of the ethanol extract of betel leaf was assayed following the method reported previously by Shibata et al (1995) 28 , and Ohno et al, (2003) 29 with slight modification. The 50mM citrate-phosphate buffer (pH 5.0), 50mM Phosphate buffer (pH 7.0), 20mM Tris-HCl buffer (pH 9.0) and 20mM Glycine-NaOH buffer (pH 10.0) were used in this assay.…”
Section: Antibacterial Activity At Different Ph Valuesmentioning
confidence: 99%